FINITE ELEMENT CALCULATION ANALYSIS OF A LARGE THREE-ROW ROLLER SLEWING BEARING - HUANG LongYi; FU Hang; WANG Yu; WANG Hua; JI Xu (Jixie qiangdu)
To raise the efficiency of finite element calculation of load distribution in large three-row roller slewing bearing, an equivalent modeling method using the combination of shell element and nonlinear spring element was proposed on the basis of the structural features of the assembly. The spring element was used to replace the load and deformation behavior of roller, and the shell element was used to simulate the contact area between the roller and raceway contact. The computational scale of the nonlinear contacts was reduced with this modeling approach, and the load distribution of bearing can be obtained efficiently with lower computational scale. The effectiveness of the finite element calculation model was validated with the static loading experiment. The roller-raceway contact analysis was conducted on the basis of the maximum contact load from the finite element calculation analysis. The stress distribution between the roller and raceway contact under different clearances was studied. The results show that the stress in the edge area of the roller-raceway contact increases with the increase of clearance, thus leading to the decreases of fatigue life.